Uji Stabilitas Formulasi Sediaan Gel Nano Partikel Eksktrak Etanol Daun Singkong (Manihot esculenta Crantz) - Wahyu Purwanjani; Maulita Saraswati; Gigih Kenanga Sari (Joseph: Journal of Science and Pharmacy, 2022)
Background; Peel-off gel masks are an alternative dosage form that can enhance user comfort and are expected to improve the antioxidant activity of papaya fruit. Papaya (Carica papaya) exhibits antioxidant activity due to the presence of components such as beta-carotene, vitamin C, and lycopene. Objective : This study aims to determine whether the methanol extract of papaya fruit can be formulated into a peel-off facial gel mask and to identify the optimal concentration of polyvinyl alcohol (PVA)—the main base ingredient of peel-off gel masks—that provides the best physical and chemical properties, as well as antioxidant activity with the most favorable IC50 value. Method; The extraction method used was maceration with methanol as the solvent. PVA was used at concentrations of 2.5%, 8.75%, and 17.5%. Physical property tests included organoleptic evaluation, adhesion test, and spreadability test, while chemical properties were evaluated using pH testing. Results; Based on the results, the methanol extract of papaya fruit can be successfully formulated into a peel-off facial gel mask. The formula containing 8.75% PVA met organoleptic standards, had an adhesion time of 20.16 ± 2.90 seconds, spreadability of 10.2 ± 1.28 cm, a pH value of 7.13, and an IC50 value of 80.52 µg/mL, indicating strong antioxidant activity. Conclusion : From the formulation and physical evaluation of the peel-off gel mask containing ethanol extract of tea leaves (Camellia sinensis L.), a thick brown gel with a characteristic tea leaf aroma was obtained. Evaluation results showed a pH value of 5, drying time of 20 minutes, spreadability within acceptable range, adhesion time of 8.73 seconds, and no irritation was observed during the irritation test, indicating that the peel-off gel mask is safe for use